Dermatoglyphics in Diabetic Cataract Patients: A Case Control Study - Paliwal, Dr. Rahul Omprakash; Shriram Dhule, Dr. Pankaj (International Journal of Innovative Research in Medical Science, 2018)
Objective: To study finger and palmar dermatoglyphic patterns in diabetic cataract patients, to find out whether a specific dermatoglyphic trait exists & its significance, To compare dermatoglyphic configuration of diabetic cataract patients with normal population in central India region. Material & methods: The sample constituted 200 (100 men and 100 women) patients suffering from cataract associated with diabetes mellitus, all above 40 years of age group obtained from Ophthalmology wards, of a government medical college, in central India. The age matched control group of 200 (100 men and 100 women) were obtained from general population which were normal healthy individuals with no other obvious genetic disorders, all above 40 years of age group. Dermatoglyphic prints were taken by ‘INK METHOD’ described by Cummins (1936) and Cummins and Midlo (1961) & were subjected for specific dermatoglyphic analysis with the help of magnifying hand lens. The prints obtained by ink method were studied in right and left hand separately. For statistical analysis of qualitative data 2 x 2 chi-square test and for quantitative data student’s t-test were applied. Observation & results: Increase in the frequency of pattern in 3rd interdigital area in diabetic cataract males. Also there is decrease frequency of patterns in 4th interdigital area in diabetic cataracts of both the sexes. Further hypothenar area in diabetic cataract females shows slight increase in pattern frequency. Main line index shows no significant variations in diabetic cataracts of both sexes when compared to controls. The main line formulae 11 9 7 pattern is most common pattern in both the groups. No significant variations are observed in atd angle. Total number of triradii found is significantly higher in diabetic cataract males and females as compared to controls. Conclusion: Significant variations are observed in the various dermatoglyphic parameters among normal population and persons having cataract associated with diabetes mellitus. On the basis of results obtained, the study can be used for early detection of the predisposed persons from the normal population so that they can be subjected to preventive measures, to avoid the future burden of the disease on the community.